Prévention de la délinquance : le rôle médiateur des pairs - Vitaro, Frank; Tremblay, Richard (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1998)
The objective of this study was to test whether friends' characteristics mediated the link between early reduction of disruptive behavior and later reduction of delinquency (through a prevention program). The prevention program includes two components : social-cognitive-skills training for boys and parent-skills training at home. It was applied over a two-year period when the subjects were 8- and 9-year-old. Subjects were low SES boys rated as disruptive by their kindergarten teachers. They were randomly assigned to a prevention or a control condition. Their friends ' aggressiveness was rated by classmates over a three-year period following the end of the prevention program. Subjects reported on their delinquent behaviors when they were 13- and 14-year-old. Results indicate that friends' aggressiveness partially mediated the impact of the program on preventing delinquency. However, compared to the control boys, other mediating variables might also have played a role.